2016
DOI: 10.2147/ijhts.s70362
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput approaches for genotoxicity testing in drug development: recent advances

Abstract: New molecules targeted at enhancing quality of life undergo various tests to evaluate their efficacy and biosafety before approval. However, there is an urgent need to develop a standardized set of tests and regulatory standards to ensure all molecules comply with biosafety standards at all stages. Though there is a battery of tests used to assess the toxicity of various compounds under study, the inability of these tests to yield a consensus serves as a major drawback. In addition, the time-consuming and labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…To identify mutagenicity of a substance, the AMES toxicity test uses multiple strains of Salmonella typhimurium bacteria with a gene mutation in the production of histidine [41]. Mitragynine tested negative in the AMES toxicity test, suggesting that it is nonmutagenic.…”
Section: Adme and Toxicity Studiesmentioning
confidence: 99%
“…To identify mutagenicity of a substance, the AMES toxicity test uses multiple strains of Salmonella typhimurium bacteria with a gene mutation in the production of histidine [41]. Mitragynine tested negative in the AMES toxicity test, suggesting that it is nonmutagenic.…”
Section: Adme and Toxicity Studiesmentioning
confidence: 99%
“…More and more industries integrate sustainability and safety to their research and development, which implies to consider the use of a safe-by-design approach (Schwarz-Plaschg et al 2017). In this respect, high throughput screening (HTS) genotoxicity testing can present lots of advantages (Sukumaran et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of a genotoxic compound may vary from the intervention in the various proteins that are involved in the replication process and maintenance of chromosomal activity. A genotoxic compound may also possess a property that causes mutations and breaks in the deoxyribonucleic acid (DNA) structure (Ranganatha et al, 2016). Many of the discovered drugs used to treat cancer (Gwozdzinski and Lichota, 2018;Swift and Golsteyn, 2014), microbial infection (Brambilla et al, 2012;Galdiero et al, 2016), wound (Mattana et al, 2014) and inflammation (Brambilla and Martelli, 2009) have demonstrated genotoxic properties.…”
Section: Introductionmentioning
confidence: 99%